Leukemia cutis - Angoori G Rao; Indira Danturty (Wolters Kluwer Medknow Publications, 2012)
Leukemia cutis is the infiltration of neoplastic leukocytes or their precursors into the epidermis, the dermis, or the subcutis, resulting in clinically identifiable cutaneous lesions. Leukemia cutis may follow, precede or occur concomitantly with the diagnosis of systemic leukemia. A 50-year-old woman presented with asymptomatic multiple cutaneous nodules all over the body of 4 months duration. Cutaneous examination showed multiple hyperpigmented nodules and plaques involving face, trunk, and extremities. Peripheral smear showed abnormally elevated leucocyte count (TLC-70,000) with abnormal cells: myeloblasts 40%, promyelocytes 8% and myelocytes 39%. Auer rods were present in few myeloblasts. Bone marrow aspiration showed increased cellularity, erythroid hyperplasia with megaloblastic change, increased myeloblasts with maturation arrest. Immunohistochemistry showed strongly positive myeloperoxidase infiltrating cells and negative for CD20 and CD3 consistent with the diagnosis of AML-M 2 with leukemia cutis. This case is reported for its rarity.